Globalization and Mass Media Exposure among the Youth of AWGP - SHREEPAL CHAUHAN (Dr. Chinmay Pandya, 2017)
Globalization may be thought initially as the widening, deepening and speeding up of worldwide interconnectedness in all aspects of contemporary social life, from the cultural to the criminal, the financial to the spiritual. This definition suggests that at the most general level, globalization refers to a process of change, which affects all regions of the world in a variety of sectors including the economy, technology, politics, the media, culture and the environment. Mass Media is playing a crucial role in today's human society. It has become a powerful instrument of social change and influences the daily life of the people. New communication technologies such as satellites, cable television, wireless telephony, the Internet and computers are bringing about noticeable changes in the modern society. The present paper is based on an empirical research study conducted on 100 Youth trainees of a Prashikshan Shivir (Training Camp) of All World Gayatri Pariwar, Shantikunj, Haridwar by administrating an interview schedule on the respondents. The exploration of the present study reveals that most of the persons associated with this type of training are youth coming from upper and middle order caste backgrounds. In order to know their place of origin data suggests that there were twelve states representation in the study and mass media exposure of the respondents was very high.